Empowering managers : a framework for developing and sustaining manager-as-coach competencies for long-term impact - Lattuca, Tracy; Hewitt, L.M.M.; Coetzee, Olga (International Journal of Evidence Based Coaching and Mentoring)
Despite the benefits to individuals, managers and organisations, and the investment organisations make to develop managers to coach, the number of coaching managers remains limited. Regrettably, those who coach, coach infrequently, as many do not possess the requisite skills, receiving little training that is often designed and delivered by external coaches who lack managerial experience. Using Interpretative Phenomenological Analysis (IPA), this study explores the lived experiences of nine managers and makes sense of their rich coaching narratives to develop a comprehensive, evidence-based manager-as-coach framework to educate managers to coach and sustain coaching as a practice. The framework provides a flexible scaffolding to customise manager-as-coach educational programmes for organisations and individual managers.